On the quasi-stationary distribution of the stochastic logistic epidemic - Nåsell, Ingemar (Mathematical biosciences, 1999)
An approximation is derived for the quasi-stationary distribution of the stochastic logistic epidemic in the intricate case where the transmission factor R 0 lies in the transition region near the deterministic threshold value 1. An approximation for the expected time to extinction from quasi-stationarity in the same parameter region is also given. Mathematics subject classification: 60J27; 92D30